Tagang System Development: The Impacts and Perception of Local Communities in Terbat Mawang Village, Sarawak, Malaysia - Nur Zaimah, Ubaidillah; Restiweella, Saib; Rossazana Ab-Rahim, Ab-Rahim; Farhana, Ismail (Human Resource Management Academic Research Society (HRMARS), 2018)
Growing in popularity of tourism industry in Sarawak creates opportunities for economic development. This industry has been recognized as one of the sectors that contribute to the economic growth in the state. The number of tourists willing to visit the unexplored nature and different cultures has sparked and increased the development for the ecotourism industry. This study focuses on the impacts and perception of local communities on Tagang system development in Terbat Mawang Village, Sarawak. The respondents' feedback was analysed using factor analysis and reliability test. The study showed that three subscales components were identified including economic impact, conservation and protection, and ecotourism benefits in the analysis. In short, the socioeconomic and environmental implications captured an excellent opportunity for economic development in the ecotourism industry.